(untitled) (Bangladesh Journal of Botany, 2021)
Ten commercial genotypes of Gerbera jamesonii were evaluated for a number of qualitative and quantitative traits in RCBD at the Botanical Garden of Jahangirnagar University, Savar, Dhaka. Qualitative morphology among 10 genotypes showed significant similarities and dissimilarities. The analysis of variance for all the quantitative traits showed highly significant variations among the genotypes. Genotypes Dutch Diva, Classic Fabio Gold, Candela and Dune proved to be the most suitable and sustainable as they were the best performer for different growth and flower quality parameters. Number of flowers per plant found best in Candela and Dutch Diva (11.33). The phenotypic coefficients of variation (PCV) were found higher than the genotypic coefficients of variation (GCV) for all characters. Maximum GCV and PCV were observed for number of suckers per plant (30.984 and 39.568) followed by number of whorls of ray florets per flower and days to flowering from bud initiation. High heritability values were obtained for all the characters. In high heritability estimate coupled with high genetic advance as percentage of mean was maximum for days to first flowering (32.442), plant height (cm) (17.026) and number of suckers per plant (15.992). Selection would be effective for the character showing high performance in genetic parameter. Path analysis revealed that the diameter of disc florets per flower, stalk girth (cm), number of disc florets per flower, number of ray florets per flower would be selection criteria for improvement in flower number. Based on D2 statistics, 10 genotypes were grouped into 3 clusters, namely cluster I, II and III. Highest number of genotypes was found in cluster I containing 5 genotypes. Scatter diagram represents pattern of genotypic distribution into clustering through principal component scores. Highest inter-cluster distance (22.94) was observed between cluster I and III. The genotypes of cluster II possessed heterogeneous nature and showed highest intra-cluster distance (11.35). Highest cluster mean was observed in cluster II containing four genotypes regarded as the superior than another cluster. Bangladesh J. Bot. 50(3): 541-550, 2021 (September)